MYOMECTOMY AT CAESAREAN SECTION: DESCRIPTIVE STUDY OF CLINICAL OUTCOME IN A TROPICAL SETTING - Adesiyun, Adesiyun; Gbadebo, Adebiyi; Ameh, Ameh; Charles, A.; Ojabo, Ojabo; Austin, Austin (Journal of Ayub Medical College Abbottabad, 2009)
Background: In the tropics, leiomyoma are commonly encountered in women of the reproductive age group, although they are mostly asymptomatic. Surgery for uterine fibroid at caesarean section has remained controversial.Objective: To analyse the clinical outcome of women that had selective caesarean myomectomy in a community teaching hospital. Method: Twenty-two women that had selective myomectomy at caesarean section between January 2002 and October 2007 were analysed. Results: The patients mean age was 31.5 years with age range of 27-44 years. Of the 22 patients, 16 (72.7%) were Primigravida, 19 (86.4%) of the patients had caesarean section at term, 2 (9.1%) and 1 (4.5%) of the patients were preterm and post term respectively. A significant number of the patients (16/22, 72.7%) had elective caesarean section and the remaining 6 (27.3%) patients had emergency caesarean section. The 3 leadingindications for caesarean section among the patients were malpresentation/abnormal lie 36.4%, uterine fibroids 18.2%, and a previous caesarean section with complication in 13.6% of the patients. Indications for myomectomy at caesarean section were fibroid in lower uterine segment in15 (68.2%) patients, pedunculated uterine fibroid in4 (18.2%) patients and anterior subserous fibroid in 3 (13.6%) patients. Intraopertively in the 22 patients, 10 (45.5%) had fibroid(s) removed only in the lower uterine segment; while 6 (27.3%) patients each, had it removed in the upper uterine segmentand both upper and lower uterine segmentsrespectively. A total of46 fibroids were removed in the22 patients, of which 24 (52.2%) were subserous/pedunculated, 16 (34.8%) intramural and 6 (13.0%) were submucous. Of the 46 fibroids, 32 (69.9%) were between 6 to 10 cm size. Sixteen (72.2%) of the 22 patients lost between 751 to 1000 ml of blood intraoperatively with an average of 806.8ml of blood loss. Two(9.1%) of the 22 patients hadblood transfusion due to anaemia. Other complications encounteredwere puerperal pyrexia and sepsis in 2 (9.1%) patients, and fracture of the humerus and clavicle of the baby in 1 (2.3%) patient. There was no maternal and perinatal mortality. Conclusion: Selection of patients for caesarean myomectomy reduces blood loss, anaemia and other complications. Keywords: Myomectomy; Uterine fibroids; Caesarean section